EVALUATION OF FINANCIAL EFFECTS OF PUBLIC PROCUREMENT CENTRALISATION - Šerpytis, Karolis; Vengrauskas, Vytautas; Gineitienė, Zinaida (Ekonomika, 2011)
One of the main goals of public procurement centralization is to generate monetary savings directly impacting the total costs of public institutions. It seems to be a remedy in economic downturn, but the impact of centralization may have both positive and negative financial effects. A central procurement organisation constitutes an additional link in the supply chain that makes the distance between the buyer and the supplier longer. Therefore, the existence of this link should be justified, and the evaluation of centralisation impact is one of the key tools in ensuring the procurement centralisation decisions to be beneficial to the state. The aim of the study was to formulate the model which would serve as a basis for evaluating the financial impact of centralised public procurement.